PERANCANGAN SISTEM INFORMASI BILLING ONLINE BERBASIS WEB PADA PERUSAHAAN PENGELOLA KAWASAN INDUSTRI XYZ - Samin Samin; Imam Yunianto (Institut Bisnis Muhammadiyah Bekasi, 2022)
The online Billing information system at the XYZ Industrial Estate Management company is a system that will improve the performance of the billing system that runs, among other things, accelerating the sending of bills to tenants as customers. Make it easier to file tenant bill files and reduce paper usage for billing dues to tenants. The Biling Online information system at the XYZ industrial estate management company also makes it easier for tenants to see the number of bills to be paid.